2017
DOI: 10.1103/physrevb.95.024311
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of lattice thermal conductivity in crystalline phase change materials: GeTe, Sb2Te3 , and Ge2

Abstract: Thermal transport is a key feature for the operation of phase change memory devices which rest on a fast and reversible transformation between the crystalline and amorphous phases of chalcogenide alloys upon Joule heating. In this paper we report on the ab initio calculations of bulk thermal conductivity of the prototypical phase change compounds Ge 2 Sb 2 Te 5 and GeTe in their crystalline form. The related Sb 2 Te 3 compound is also investigated for the sake of comparison. Thermal conductivity is obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
89
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 57 publications
19
89
0
2
Order By: Relevance
“…In this work we have not included long-range dispersion forces; instead, we have chosen to use PBESol exchange-correlation functional to improve accuracy on the lattice parameters. It has been shown that negative frequencies reported for GST225 become positive once the overestimation of the c parameter is reduced closer to experimental values [31]. Here we report that the use of the PBEsol xc functional improves the agreement of lattice parameters of GST225 with respect to experimental measures, which leads to similar results as those obtained by Campi et al through van der Waals interactions [31].…”
Section: (Gete) 1 (Sb 2 Te 3 ) (Gst124)supporting
confidence: 78%
See 4 more Smart Citations
“…In this work we have not included long-range dispersion forces; instead, we have chosen to use PBESol exchange-correlation functional to improve accuracy on the lattice parameters. It has been shown that negative frequencies reported for GST225 become positive once the overestimation of the c parameter is reduced closer to experimental values [31]. Here we report that the use of the PBEsol xc functional improves the agreement of lattice parameters of GST225 with respect to experimental measures, which leads to similar results as those obtained by Campi et al through van der Waals interactions [31].…”
Section: (Gete) 1 (Sb 2 Te 3 ) (Gst124)supporting
confidence: 78%
“…It has been shown that negative frequencies reported for GST225 become positive once the overestimation of the c parameter is reduced closer to experimental values [31]. Here we report that the use of the PBEsol xc functional improves the agreement of lattice parameters of GST225 with respect to experimental measures, which leads to similar results as those obtained by Campi et al through van der Waals interactions [31]. Table II summarizes our relaxed structure parameters together with the available experimental data.…”
Section: (Gete) 1 (Sb 2 Te 3 ) (Gst124)supporting
confidence: 77%
See 3 more Smart Citations